2021
DOI: 10.1096/fj.202002745r
|View full text |Cite
|
Sign up to set email alerts
|

Late adolescence mortality in mice with brain‐specific deletion of the volume‐regulated anion channel subunit LRRC8A

Abstract: The leucine-rich repeat-containing family 8 member A (LRRC8A) is an essential subunit of the volume-regulated anion channel (VRAC). VRAC is critical for cell volume control, but its broader physiological functions remain under investigation. Recent studies in the field indicate that Lrrc8a disruption in the brain astrocytes reduces neuronal excitability, impairs synaptic plasticity and memory, and protects against cerebral ischemia. In the present work, we generated brainwide conditional LRRC8A knockout mice (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 107 publications
2
16
0
Order By: Relevance
“…Also, a number of disorders are found in recent studies using specific cell- or tissue-targeted Lrrc8a knockout mice. For example, impaired glucose tolerance and insulin resistance are caused by conditional knockout of Lrrc8a expressing in adipocytes ( Zhang et al, 2017 ), pancreatic β cells ( Kang et al, 2018 ), and skeletal muscle cells ( Kumar et al, 2020 ); male infertility by germ cell-specific Lrrc8a disruption ( Lück et al, 2018 ); angiotensin-II-stimulated hypertension by endothelial-targeted Lrrc8a knockout ( Alghanem et al, 2021 ); and brain hyperexcitability coupled to astrogliosis by brain-specific Lrrc8a disruption ( Wilson et al, 2021 ). However, it is not known whether these dysfunctions are caused by disordered anion-conductive activities of LRRC8A or non-conductive protein-protein interactions.…”
Section: Perspectivementioning
confidence: 99%
“…Also, a number of disorders are found in recent studies using specific cell- or tissue-targeted Lrrc8a knockout mice. For example, impaired glucose tolerance and insulin resistance are caused by conditional knockout of Lrrc8a expressing in adipocytes ( Zhang et al, 2017 ), pancreatic β cells ( Kang et al, 2018 ), and skeletal muscle cells ( Kumar et al, 2020 ); male infertility by germ cell-specific Lrrc8a disruption ( Lück et al, 2018 ); angiotensin-II-stimulated hypertension by endothelial-targeted Lrrc8a knockout ( Alghanem et al, 2021 ); and brain hyperexcitability coupled to astrogliosis by brain-specific Lrrc8a disruption ( Wilson et al, 2021 ). However, it is not known whether these dysfunctions are caused by disordered anion-conductive activities of LRRC8A or non-conductive protein-protein interactions.…”
Section: Perspectivementioning
confidence: 99%
“…Previously, we found that the brain-wide deletion of LRRC8A reduced astrocytic expression of the glutamate transporter GLT-1. 31 Therefore, we additionally explored if there were changes in GLT-1 immunoreactivity in the iaLRRC8A KO but no differences were detected in any of the tested groups ( Figures 1 H and 1I; primary images in Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This assay, which has been thoroughly validated using RNAi and pharmacological tools, quantifies the activity of the LRRC8A-containing VRAC in large populations of astrocytes and gives comparable results to electrophysiological recordings of VRAC Cl − currents. 31 , 36 , 37 Hypoosmotic challenge of cultured astrocytes stimulated glutamate (D-[ 3 H]aspartate) release via VRAC, and such release was reduced by approximately 70% in the tamoxifen-treated iaLRRC8A KO cultures as compared to the DMSO-treated controls from the same genotype ( Figure 2 D). Taken together, the results of our in vivo and in vitro experiments suggest that we successfully downregulated LRRC8A expression in brain astrocytes and that such downregulation was associated with a significant loss of VRAC activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, defects of connexins have also been linked to myelin vacuolization [ 39 ]. As LRRC8 proteins of VRAC channels are involved in cell volume regulation and their absence cause cell vacuolation in several tissues, it will be important to analyse whether a conditional (because the complete KO is deleterious [ 40 ]) astrocyte KO of LRRC8A [ 41 ] (the main constituent of the VRAC channel [ 42 , 43 ]) also displays astrocyte and myelin vacuolization.…”
Section: Physiological Processes Affected In Mlc Deduced From Animal ...mentioning
confidence: 99%